Boko Haram: At the Intersection of Regional Security Complexes, Islamism and Gender Dynamics - Solomon, Hussein (Scientia Militaria - South African Journal of Military Studies, 2025)
Boko Haram has been in existence since 2002. In its more than two decades, it has been the scourge of the region bringing death, destruction and displacement to vast swathes of Nigeria and neighbouring states. Despite strenuous efforts on the part of the Nigerian state, neighbouring countries and the international community, the carnage and breadth of human suffering have grown in intensity as Boko Haram and its offshoots have continued to extend their tentacles into new territories. Despite intense rivalries between Boko Haram and its Islamist rivals, and counter-terrorism efforts, the extremist challenge posed has escalated. Why is this so? Three factors contributed to this failure. First, the research on which this article is based, found that the phenomenon of Boko Haram needs to be understood beyond the borders of Nigeria – as part of a dynamic regional security complex. Second, because analysts under-played the importance of Islamist ideology, the nature of the beast was misunderstood. Policy measures undertaken, based on this misdiagnosis, were then bound to fail. Third, counter-terrorism efforts have also failed due to an important omission – failing to see the relationship between misogyny and extremism.